An Econometric Study on the Determinants of Economic Growth in Nepal - Sigdel, Sahadev (Journal of Kathmandu BernHardt College, 2025)
This study examines the determinants of economic growth in Nepal, focusing on the role of financial variables; bank lending, deposits, investment, and interest rates for the study period 2009 to 2023. Using secondary data from Nepal Rastra Bank and World Bank sources, the study employs correlation analysis, Ordinary Least Squares (OLS) regression, Johansen co-integration, and the Error Correction Model (ECM) to explore both short and long-run relationships. Empirical results reveal that GDP growth is strongly and positively influenced by bank lending t-statistics (t) = –3.27, probability (p) = 0.03), deposits (t = –5.51, p = 0.00), and investments (t = –4.91, p = 0.00), while higher interest rates (t = –4.72, p = 0.00) constrain growth by increasing borrowing costs. Short-run effects are limited, but the ECM’s significant error correction term (–0.5006, p = 0.038) indicates rapid adjustment toward long-run equilibrium. Diagnostic tests confirm model robustness, showing no serial correlation, heteroskedasticity, or deviation from normality. The findings underscore that Nepal’s economic growth is predominantly driven by sustained financial intermediation and banking sector development, highlighting the need for policies that strengthen credit mobilization, investment financing, and inclusive financial access. It is recommended that policymakers focus on enhancing banking sector efficiency and expanding financial outreach to sustain long-term economic growth.